STRUKTUR MITOS CUPU KYAI PANJALA DI PADUKUHAN MENDAK: TINJAUAN ETNOLINGUISTIK - Die Bhakti Wardoyo Putro (CARAKA, 2018)
This study aims to describe (1) the structure of the myth of the kyai Panjala cupu, (2) the meaning of the ritual of the cupu kyai panjala, and (3) the mindset, the view of life, and the worldview of the Mendak community. This research is a type of qualitative research with an ethnolinguistic approach. This research data is in the form of words in the myth kyai cupu panjala. Data analysis uses an etnosains model and is presented through formal and informal methods. The results of this study are (1) the structure of the myth of the Kyai Panjala Cupu which is divided into four episodes; (2) the meaning of denotation and the meaning of leksi in the kyai cupu panjala ritual; and (3) the mindset of the people of Menduk seen in the form of their daily behavior, namely hard work, caution, guarding, and being in harmony with nature. The public view that humans were created as individual beings and social beings. The world view by the Mendak community that this world does not exist with its inheritance, but there are those who hold and who control as the supreme ruler, namely God.